Structural and Functional Asymmetry in Precentral and Postcentral Gyrus in Patients With Unilateral Chronic Shoulder Pain - Wei, Xiaoya; Shi, Guangxia; Tu, Jianfeng; Zhou, Hang; Duan, Yanshan; Lee, Chin Kai; Wang, Xu; Liu, Cunzhi (Frontiers in Neurology, 2022)
Objective The purpose of this study was to explore the structural and functional asymmetry of precentral and postcentral gyrus in patients with unilateral chronic shoulder pain (CSP) utilizing MRI. Patients and Methods We collected structural and resting-state functional MRI (rs-fMRI) data in 22 left-sided, 15 patients with right-sided CSP, and 24 healthy controls (HCs). Here, we performed the structural asymmetry and seed-based functional connectivity (FC) analyses. We extracted regional cortical thickness and surface area measurements from T1-weighted MRI images, using asymmetry indexes (AIs) to assess asymmetries. We used Data Processing and Analysis for Brain Imaging software for seed-based FC analysis and selected unilateral-precentral and postcentral as the regions of interest. Then, we performed group comparisons of the neuroimaging metrics, and also explored the relationships between brain asymmetry and clinical variables. Results We found significant differences in surface area AIs of the precentral among three groups, the AI values were negatively correlated with the visual analog scale score and positively correlated with Constant–Murley scores (CMS) in the left-sided CSP group. Further, FC of left postcentral with cingulate gyrus and left paracentral lobule showed significant group differences; FC of right postcentral with left caudate, left paracentral, and left postcentral were different among groups; FC of right precentral with the cingulate gyrus, precuneus, and left paracentral revealed significant group differences. Besides, there was a positive correlation between right precentral-cingulate gyrus FC and CMS in the right-sided CSP group. Conclusion Surface area and FC patterns asymmetry exist in precentral and postcentral gyrus in patients with unilateral CSP. Asymmetry trend is associated with pain severity and shoulder joint function impairment. Brain structural and functional asymmetry may be an important indicator for understanding the potential mechanism of chronic pain.